Assessment of Renal Functions among Saudi Arabian Pregnant Women in Jazan Region - Al-Elsukar, Akram Hamed Awad; Ahmed, Ahmed Mohammed (Arab Journal for Sciences and Research Publishing, 2015)
Marked renal hemodynamic changes are apparent by the end of the first trimester. Both the Glomerularfiltration rate and effective renal plasma flow increase by 50% of pregnant women. Effective renal plasma flow probablyincreases to a greater extent, and thus, the filtration fraction is decreased during early and mid-pregnancy. Objectives: To assessthe serum levels of renal functions among Saudi Arabian Pregnant women in Jazan region.Materials and Methods: a prospective, case- control hospital based study conducted in Jazan region from March 2014– June 2015.30 pregnant womenselected in Jazan General Hospital and assessed for renal function tests. 30 healthy subjects selected as control group who wereage, and socioeconomic matched to the pregnancy group. SPSS was used for data analysis using student’s ‟t” test and Pearson'scorrelation for assessment of correlation between different variables.Results: There was a significant difference in the mean of the serum levels of urea and creatinine in test group (p
Keywords: Pregnancy; Urea and Creatinine